{2}*\sqrt[4]{8} =\sqrt[4]{16}=2\\\frac{\sqrt[3]{54} }{\sqrt[3]{2}} =\sqrt[3]{27} =3\\(2-\sqrt[3]{6} )(4+2*\sqrt[3]{6}+\sqrt[3]{36})=(2-\sqrt[3]{6} )(4+2*\sqrt[3]{6}+\sqrt[3]{6^2})=2^3-(\sqrt[3]{6})^3=8-6=2" alt="5+\sqrt[3]{-64} =5-4=1\\4+\sqrt[4]{81} =4+3=7\\\sqrt[4]
{2}*\sqrt[4]{8} =\sqrt[4]{16}=2\\\frac{\sqrt[3]{54} }{\sqrt[3]{2}} =\sqrt[3]{27} =3\\(2-\sqrt[3]{6} )(4+2*\sqrt[3]{6}+\sqrt[3]{36})=(2-\sqrt[3]{6} )(4+2*\sqrt[3]{6}+\sqrt[3]{6^2})=2^3-(\sqrt[3]{6})^3=8-6=2" align="absmiddle" class="latex-formula">
![\frac{3}{\sqrt[3]{5}} =\frac{3}{5}} \sqrt[3]{25} \frac{3}{\sqrt[3]{5}} =\frac{3}{5}} \sqrt[3]{25}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B%5Csqrt%5B3%5D%7B5%7D%7D%20%3D%5Cfrac%7B3%7D%7B5%7D%7D%20%5Csqrt%5B3%5D%7B25%7D)
![\frac{6}{\sqrt[3]{5} +1} =\frac{6*(\sqrt[3]{5^2}-\sqrt[3]{5}+1)}{5+1} =(\sqrt[3]{5^2}-\sqrt[3]{5}+1) \frac{6}{\sqrt[3]{5} +1} =\frac{6*(\sqrt[3]{5^2}-\sqrt[3]{5}+1)}{5+1} =(\sqrt[3]{5^2}-\sqrt[3]{5}+1)](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B%5Csqrt%5B3%5D%7B5%7D%20%2B1%7D%20%3D%5Cfrac%7B6%2A%28%5Csqrt%5B3%5D%7B5%5E2%7D-%5Csqrt%5B3%5D%7B5%7D%2B1%29%7D%7B5%2B1%7D%20%3D%28%5Csqrt%5B3%5D%7B5%5E2%7D-%5Csqrt%5B3%5D%7B5%7D%2B1%29)
![\frac{3}{\sqrt[3]{16}} +\sqrt[3]{4} +1=\frac{3}{2*\sqrt[3]{2}} +\sqrt[3]{4} +1=\frac{3}{4} \sqrt[3]{4} +\sqrt[3]{4} +1=1,75*\sqrt[3]{4} +1 \frac{3}{\sqrt[3]{16}} +\sqrt[3]{4} +1=\frac{3}{2*\sqrt[3]{2}} +\sqrt[3]{4} +1=\frac{3}{4} \sqrt[3]{4} +\sqrt[3]{4} +1=1,75*\sqrt[3]{4} +1](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B%5Csqrt%5B3%5D%7B16%7D%7D%20%2B%5Csqrt%5B3%5D%7B4%7D%20%2B1%3D%5Cfrac%7B3%7D%7B2%2A%5Csqrt%5B3%5D%7B2%7D%7D%20%2B%5Csqrt%5B3%5D%7B4%7D%20%2B1%3D%5Cfrac%7B3%7D%7B4%7D%20%5Csqrt%5B3%5D%7B4%7D%20%2B%5Csqrt%5B3%5D%7B4%7D%20%2B1%3D1%2C75%2A%5Csqrt%5B3%5D%7B4%7D%20%2B1)